On the concept and legal nature of conditional conviction - Bizhanova, А.Р.; Kenzhibekova, Э.П.; Osmanova, Г.Ж. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
In the context of transforming criminal policy, there is a humanization of the convicts detention conditions in places of deprivation of liberty, implementation of international legal acts in criminal and penal enforcement legislation, and expansion of the scope of applying alternative non-penitentiary sanctions. With the implementation of the new criminal legislation, the number of ‘prison population’, the bulk of which accounts for the use of conditional sentences, has decreased. The importance of this conditional sentence is due to the fact that reducing crime does not necessarily entail changes in the nature of punishment in the direction of strengthening the role of persuasion and the influence of organizations. These changes have been implemented through legal institutions that economically spend criminal repression, mitigating the coercive effects of punishment. Within the framework of legal science theory, there are different views on the legal nature of a conditional sentence. Therefore, due to the lack of a unified approach to solving issues related to the establishment of the grounds for the use of the institution of probation, the conditions performed by convicts during probation control, the determination of criminal record, the removal of criminal record, difficulties may arise. Moreover, in recent years, most of the repeat offenders have been conditionally convicted. All this actualized the issue of improving the institution of probation. Taking into account the theoretical and practical significance of the correct definition of the legal nature of a conditional sentence, the authors consider the concept of a conditional sentence and its legal nature and analyze various points of view of researchers, as well as explain the reasons for the appointment and refusal of a conditional sentence.